Lens Thickness with Age and Accommodation by Optical Coherence Tomography - Richdale, Kathryn (2008)
PURPOSE: To utilize time-domain optical coherence tomography (OCT) to measure changes in the crystalline lens with age and accommodation. METHODS: A cross-sectional study of pre-presbyopic and presbyopic subjects was conducted. Amplitude of accommodation was measured with the push-up test. Objective accommodation was measured with the Grand Seiko auto-refractor and a Badal lens system. Lens thickness was measured with the Zeiss Visante OCT and an internal optometer. The data were analyzed using correlation coefficients, linear regression, and by calculating the average change in lens thickness per diopter change in objective accommodation. RESULTS: Twenty-two subjects between the ages of 36 and 50 years completed the study. Subjective amplitude of accommodation ranged from 2.17 to 6.38 D. Objective accommodation ranged from 0.22 to 4.56 D. The mean lens thickness was 4.05 ± 0.20 mm. The mean change in lens thickness for up to a 5-D accommodative stimulus ranged from 0.01 to 0.26 mm. The correlation coefficients were: age and subjective accommodation, r = −0.74; age and objective accommodation, r = −0.84; change in lens thickness and age, r = −0.65; change in lens thickness and subjective accommodation, r = 0.74; change in lens thickness and objective accommodation, r = 0.64; objective and subjective accommodation, r = 0.82; (all p < 0.01). An increase in lens thickness of 21 μm per year of age was determined by linear regression. For the subjects who showed at least 1 D of accommodative response on the Grand Seiko auto-refractor, there was an increase of 51 ± 19 μm per diopter of accommodation. CONCLUSIONS: OCT is a non-invasive technique that can be used to quantify changes in the thickness of the crystalline lens. Subjective and objective measurements of accommodation, as well as age, were robustly correlated with the measured changes in lens thickness. Lens thickness changes with age and accommodation as measured with the Visante OCT compare well with previous findings using Scheimpflug photography and ultrasound.